PECULIARITIES OF FAMILY CONCEPTS OF CHILDREN DEPRIVED OF PARENTAL CARE - Krupnik, Ivan (PSYCHOLOGICAL JOURNAL, 2017)
In the article peculiarities of family concepts of children deprived of parental care are considered. The importance of choosing of an age category for qualitative research of the peculiarities of family concepts is emphasized. The technics used in the study are characterized. Ideas about the family are very important in the picture of the child’s world, because the planning of his future life depends on them. The concept of the family, attitudes, expectations have a great influence on the relationship in the family in the “husband-wife” and “parent-child” systems. The absence of a family is a deprivational factor, which negatively affects the form of family concept, namely, the positive perception of the future marriage, its formation, attitude to parental responsibilities. Comparative analysis of the results of empirical research of features ideas about future family life of children from full families and children deprived of parental care, has allowed to reveal significant differences, namely: it is established that the results of the indicators of orphan children received as a result of psychodiagnostic examination, significantly differ from those of respondents from the other sample, indicating the dependence features of family of representations of teenagers deprived of parental care, the influence of family deprivation. Significant differences in family representations of children from their families and children deprived of parental care relating to as a preventive of satisfaction with the marriage, demand for children and the image of the future family. Children deprived of parental care observed indifference to their offspring, which manifests itself in a negative attitude to child care, her discipline, to perform household duties. The idea of the future family, children deprived of parental care worse formed, less positive, intense situations of interaction between spouses and between children and parents. The prospects of further researches are seen in a thorough examination of factors that affect perceptions of children deprived of parental care, family life and the development on this basis, the psychological support of adolescents in this category.